Predictors of appropriate breastfeeding knowledge among pregnant women in Moshi Urban, Tanzania: a cross-sectional study. Issue 1 (December 2016) - Hashim, Tamara; Mgongo, Melina; Katanga, Johnson; Uriyo, Jacqueline; Damian, Damian; Stray-Pedersen, Babill; Wandel, Margareta; Msuya, Sia
Abstract Background Knowledge on infant feeding among pregnant women is essential when promoting optimal breastfeeding practices. This study aimed to assess the knowledge of women on optimal breastfeeding during pregnancy and associated factors as well as performance of the health system in reaching women with information on breastfeeding and infant feeding issues. Methods A cross-sectional study was conducted from October 2013 to April 2014 among pregnant women, in their third trimester, attending for routine care at two primary health care facilities in Moshi urban, northern Tanzania. Results A total of 536 women were enrolled, with mean age of 25.9 (SD 5.7) years. Only 51% (n  = 274) reported to have received counselling on breastfeeding from their healthcare providers during the current pregnancy. More than seven out of ten pregnant women were knowledgeable about key issues regarding appropriate breastfeeding practices: importance of colostrum (95%), time of breastfeeding initiation (71%), exclusive breastfeeding (EBF) (81%), and time of introducing complementary feeding (83%). Receiving counselling on breastfeeding during the current pregnancy (Adjusted Odds Ratio [AOR] 3.7; 95% Confidence Interval [CI]: 2.4, 5.7), having two children (AOR 2.6; 95% CI: 1.5, 4.4), having three or more children (AOR 3.5; 95% CI: 1.8, 6.9) and intention to breastfeed the child exclusively (AOR 3.6; 95% CI: 2.0, 6.5) were significantly associated with appropriate breastfeeding knowledge. Conclusions The health system failed to reach the 49% of women who did not receive counselling on infant feeding. Pregnant women who had received counselling on optimal breastfeeding and women with more than one child were more likely to have knowledge of optimal breastfeeding practices.